Mocked and shamed: Satirical news and its effects on organizational reputation - LIM, Lisbeth (Institutional Knowledge at Singapore Management University, 2019)
With fake news the rage (Tavernise, 2016), this study examines one form of fake news, satire news (Reilly, 2010). This study examines factors that lead satire news to be created, how they are used to criticize organizations and the impact on reputations. News on five satire news sites – The Onion (US), New Nation (Singapore), The Shovel (Australia), NewsThump (UK), and Der Postillon (Germany) – were analyzed using social media monitoring tools. Findings suggested that crises or paracrises (Coombs & Holladay, 2012) were likely to be exacerbated. While its effects are not immediate, satire news may have impact on organizations’ reputations over time. Satirical news sites have increased in recent years (Koziol, 2014). Insights add to understanding of the phenomenon of fake news. Anchored on the contingency theory of strategic conflict management (Pang, Jin, & Cameron, 2010), a framework for organizational response is proposed for practitioners to use.